TEACHING DIGITAL RHETORIC: BUILDING AN ARGUMENTATIVE ETHOS FOR DIGITAL MEDIA - Pascoal, Sara Cerqueira (POLISSEMA – Revista de Letras do ISCAP, 2019)
In this paper we will describe a curriculum of Rhetoric included in a Business Communication Undergraduate Program Studies at ISCAP. This curriculum includes the designing of arguments and the identification of fallacies applied to the industries of persuasion and to social media, analyzing how the success of brands depends upon the use of a strategic communication, where rhetoric plays an important role. It also emphasizes the importance of teaching and exploring the ethos, pathos and logos theory for building cogent arguments in a social media context. In addition, based on the new communication model done via various electronic formats, and considering that the internet and social media have “changed the way communicate, turning writing into conversation”, we will reflect on Paul Graham’s hierarchy of disagreement, proposing a new pyramid for ad hominem fallacies. Finally, we draw a basic collection of competencies, in order to become a more effective writer and communicator in a digitally mediated space.